Chronic ataxic neuropathy mimicking dorsal midbrain syndrome - Arbogast, S D (BMJ Group, 2007)
We describe the clinical course, with special attention to the disturbance of eye movements, of a 29‐year‐old man with chronic ataxic neuropathy with ophthalmoplegia, IgM paraprotein, cold agglutinins and anti‐GD1b disialosyl antibodies (CANOMAD). Using the magnetic search coil technique, we documented convergence during upward saccades and other features suggestive of dorsal midbrain syndrome. Thus, in common with Miller Fisher syndrome, CANOMAD may present with clinical findings implicating involvement of the central nervous system, which contains ganglioside antigens to anti‐GD1b antibodies.